O Banco Mundial, o neoliberalismo e a educação do campo no Brasil - Moretti, Monica Fernanda Botiglieri (Universidade Federal de São Carlos, 2017)
This study analyzes the participation of the World Bank in rural education projects in Brazil based on two hypotheses. Firstly, what means to a neoliberal political project justify poverty reduction and improve the living conditions of the individuals, and, secondly, in the Brazilian governments called "right" or "left", although they assume distinct political discourses, they have a lot of assumptions in common. In this way, fundamental concepts are understood and their results are fundamental for the debate that they propose to an understanding of the education elaborated for rural individuals. To do so, we use authors who discuss this theme, as well as the survey conducted with the World Bank, forming a base of research on financial projects for those who are interested in getting to know them. At the end of analytical forms we could perceive the neoliberal bias embedded in the speeches elaborated by the World Bank, as well as a trajectory of its action in the education of the Brazilian countryside. To the researchers of the area of fundamental importance for the comprehensiveness of the institution, its capillarity and influences, in this way, this study opened space for other researches in its continuity.
World Bank, neoliberalism and rural education in Brazil
Keywords: Banco Mundial; Neoliberalismo e educação; Educação do campo; World Bank; Neoliberalism and education; Rural education; CIENCIAS HUMANAS::EDUCACAO